1993
DOI: 10.1007/bf00852576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of renal nerves on renal function during development

Abstract: The present review summarizes recent studies describing the role of renal sympathetic innervation in the regulation of renal function during development. The afferent renal innervation appears early during fetal life and probably precedes the development of efferent renal nerves. There is suggestive evidence that renal nerves are required for the proper development of the kidney and that neurotrophic growth factors play an important role in renal embryogenesis and in renal tubular differentiation. Renal sympat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Afferent renal innervation occurs early in fetal life, 34 and the renal nerves are suggested to play an important role in the proper development of the kidney. 35 Thus, in this model of reduced uterine perfusion, hypoxia may serve as a stimulus for increased renal afferent nerve activity, resulting in alterations during kidney development, leading to both structural and physiological changes linked to the increased risk for development of hypertension in the adult animal.…”
Section: Discussionmentioning
confidence: 99%
“…Afferent renal innervation occurs early in fetal life, 34 and the renal nerves are suggested to play an important role in the proper development of the kidney. 35 Thus, in this model of reduced uterine perfusion, hypoxia may serve as a stimulus for increased renal afferent nerve activity, resulting in alterations during kidney development, leading to both structural and physiological changes linked to the increased risk for development of hypertension in the adult animal.…”
Section: Discussionmentioning
confidence: 99%
“…The renal nerves not only influence renal hemodynamics and renin secretion but also seem to play an inductive role during renal ontogeny (Robillard et al 1993). In vitro studies have shown that the neural element may be involved in kidney differentiation (Sariola et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical sympathectomy affects normal renal development and function, confirming that sympathetic innervation exerts a major influence on both of them (Slotkin et al 1988a(Slotkin et al , 1988bGray et al 1991). Additional studies have shown that sympathetic renal nerves modulate renal hemodynamics in early gestation and fluid/electrolyte homeostasis in late gestation (Robillard et al 1993). Furthermore, renal nerves play an important role during the transition from fetal to newborn life (Smith et al 1991Page et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, alterations in peripheral sympathetic nervous control could result in impaired renal development, as evidence suggests that the renal nerves play an important role in renal development through stimulation of the renin-angiotensin system. 29,30 Thus, asymmetric growth restriction resulting from limited growth of selective organs in late gestation, owing to alterations in nutrient supply to rapidly developing organs, may result in improper development and subsequent hypertension.…”
Section: Organ Weights In a Rat Model Of Intrauterine Growth Restrictionmentioning
confidence: 99%